Redes sociales y desarrollo de habilidades sociales en adolescentes de Primero, Segundo y Tercero de Bachillerato de la Unidad Educativa Particular Cordillera del cantón Loja. - Jiménez Maldonado, Angie Mabel (2018)
It is evident that the technology has advanced with the use of social networks, nevertheless adolescents have been attracted by online spaces. The excessive and unsupervised use of these networks has brought a deterioration in the normal development of the individual, This mainly in social skills; The main objective of this investigation was “To determine the influence of the use of social networks in the development of social skills of adolescents First, Second and Third of the baccalaureate of the Unidad Educativa Particular “CORDILLERA”, of Loja. The present research was descriptive, with a quantitative-qualitative effect, of cross-section, the results were obtained from psychometric techniques. First, a semi-structured survey about the use of social networks and later the Goldstein Social Skills Scale, moreover, It was developed with the population of 74 adolescents between 15 to 18 years old, the results was analyzed statistically through the program Startical Product and Service Solutions (SPSS). The results demonstrate, the relationship between the use of social networks in the development of social skills, For the aforementioned, the use of social networks over 2 hours in adolescents are considered excessive, Students Between first and second year use internet for 5 to 6 hours per day on the other hand, third-year high school students gain 7 or more hours, Therefore, it has been convenient to propose a psycho educational proposal this will be directed to adolescents based on the results obtained in the present research. KEY WORDS: Social Networks, Social Skills, Adolescents, technology, baccalaureate.